The Periplasmic Domain of the Ion-Conducting Stator of Bacterial Flagella Regulates Force Generation - Homma, Michio; Kojima, Seiji (Frontiers in Microbiology, 2022)
The bacterial flagellar stator is a unique ion-conducting membrane protein complex composed of two kinds of proteins, the A subunit and the B subunit. The stator couples the ion-motive force across the membrane into rotational force. The stator becomes active only when it is incorporated into the flagellar motor. The periplasmic region of the B subunit positions the stator by using the peptidoglycan-binding (PGB) motif in its periplasmic C-terminal domain to attach to the cell wall. Functional studies based on the crystal structures of the C-terminal domain of the B subunit (MotBC or PomBC) reveal that a dramatic conformational change in a characteristic α-helix allows the stator to conduct ions efficiently and bind to the PG layer. The plug and the following linker region between the transmembrane (TM) and PG-binding domains of the B subunit function in regulating the ion conductance. In Vibrio spp., the transmembrane protein FliL and the periplasmic MotX and MotY proteins also contribute to the motor function. In this review, we describe the functional and structural changes which the stator units undergo to regulate the activity of the stator to drive flagellar rotation.